Nine- to fourteen-year follow-up of implant treatment. Part I: implant loss and associations to various factors - Ann Marie Roos-Jansa°ker (journal of clinical periodontology, 2006)
Objectives: The aim of the present study was to evaluate the long-term result of implant therapy, using implant loss as outcome variable. Material and Method: Two hundred and ninty-four patients had received implant therapy (Bra°nemark System s ) during the years of 1988–1992 in Kristianstad County, Sweden. The patients were recalled to the speciality clinic 1 and 5 years after placement of the suprastructure. Between 2000 and 2002, 9–14 years after implant placements, the patients were again called in for a complete clinical and radiographic examination. Results: Two hundred and eighteen patients treated with 1057 implants were examined. Twenty-two patients had lost 46 implants and 12 implants were considered ‘‘sleeping implants’’. The overall survival rate was 95.7%. Implant loss appeared in a cluster in a few patients and early failures were most common. Eight patients lost more than one fixture. A significant relationship was observed between implant loss and periodontal bone loss of the remaining teeth at implant placement. Maxillary, as opposed to mandibulary implants, showed more implant loss if many implants were placed in the jaw. A significant relationship between smoking habits and implant loss was not found. Conclusion: A history of periodontitis seems to be related to implant loss.